The Bouzoukiâ€™s Signifiers and Significance Through the Zeibekiko Dance Song: "Evdokiaâ€™s Zeibekiko" - Saragatsis, Evangelos; Vamvakidou, Ifigeneia (European Scientific Journal, ESJ, 2017)
The objective of this study is to identify the signifiers and significance of the Zeibekiko dance, and those of the bouzouki itself, to a further extent, as they emerge through research conducted in the relevant literature, and which is anchored to those signifiers, as they are highlighted through their presence in material that is obtained from movies. The semiotic analysis of the film â€œEvdokiaâ€, by A. Damianos (1971), is the research method that is followed. In this context, the main focus is placed on the episode/scene, where Evdokiaâ€™s Zeibekiko is displayed on stage. This â€˜polytropicâ€™ (polymodal) material that consists of listening to, viewing, playing music, and dancing encompasses a large variety of musicological and gender signifiers that refer to the specific era. The model followed is that of Greimas (1996), as it was used by Lagopoulos & Boklund-Lagopoulou (2016), and Christodoulou (2012), in order to point out those characteristic features that are expressed by the bouzouki, as a musical instrument, through a representative sample of the zeibekiko dance, as it is illustrated in the homonymous film. The analysis of images, as well as of the language message, lead to the emergence of codes, such as the one referring to the gender, and also the symbolic, value, and social codes, and it is found that all these codes agree with the introductory literature research conducted on the zeibekiko dance and the bouzouki. Based on the combination of these approaches to the analysis performed, a number of elements can be clearly identified, such as the dancerâ€™s masculinity, the loneliness that characterizes the dance, the values adhered to and the respect shown to the codes of honor, and all these elements confirm the initial literature research conducted on the zeibekiko dance, and by extent, the fact that the bouzouki expresses all the above characteristics.